Theoretical approaches to food waste behaviours: An overview - Chia, Dane; Yap, Chin Choo; Aroua, Mohamed Kheireddine; Gew, Lai Ti (Applied Environmental Research, 2024)
Food waste around the world has emerged as a pressing issue that calls for attention and intervention. Analysing the food waste problem without understanding wasteful behaviour antecedents may oversimplify this multi-faceted issue, which will then compromise the development of interventions. This paper provides an overview of the theoretical approaches to food waste behaviour antecedents, followed by evidence-based interventions, using the Theory of Planned Behaviour (TPB), the Norm Activation Model (NAM), and the Social Practice Theory (SPT). These theories encompass the psychological, behavioural, societal, material, and structural factors that influence food waste practices. Our aim is to provide a holistic understanding on the antecedents of food waste behaviours and theory-based interventions.